2014
DOI: 10.1038/ijir.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

Does circumcision have a relationship with ejaculation time? Premature ejaculation evaluated using new diagnostic tools

Abstract: The aim of the study is to investigate whether there is an effect of adult circumcision on ejaculation parameters and to research the relationship between intravaginal ejaculation latency time (IELT) and premature ejaculation diagnostic tool (PEDT). Adults who underwent voluntary circumcision between September 2010 and November 2011 were enrolled in this prospective study. The IELT before and 3 months following circumcision was recorded. Also, PEDT was filled out before and 3 months after circumcision. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Some large nationally representative cross-sectional surveys24, 25 have included countries with high and low male circumcision rates, controlling for demographic factors that might influence attitudes toward circumcision. Several studies have compared intravaginal ejaculatory latency time11, 24, 25, 26, 27, 28 and a few small studies have reported direct physiologic measurements of penile sensitivity and sexual response27, 29, 30, 31 in circumcised and uncircumcised men, finding no evidence for detrimental physiologic effects of male circumcision. Two cohort studies using data from RCTs12, 13 in Africa offer the best evidence to date on the effects of VMMC on male sexual function and satisfaction, suggesting no significant impairments in sexual function or satisfaction and some improvements in sexual function after male circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…Some large nationally representative cross-sectional surveys24, 25 have included countries with high and low male circumcision rates, controlling for demographic factors that might influence attitudes toward circumcision. Several studies have compared intravaginal ejaculatory latency time11, 24, 25, 26, 27, 28 and a few small studies have reported direct physiologic measurements of penile sensitivity and sexual response27, 29, 30, 31 in circumcised and uncircumcised men, finding no evidence for detrimental physiologic effects of male circumcision. Two cohort studies using data from RCTs12, 13 in Africa offer the best evidence to date on the effects of VMMC on male sexual function and satisfaction, suggesting no significant impairments in sexual function or satisfaction and some improvements in sexual function after male circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the notion that circumcision might alter penile skin sensitivity and affect sexual function was largely de-bunked by Malkoc et al who demonstrated that the density of fine nerve endings in the foreskin of circumcised men with PE was not different from that of circumcised non-PE controls (148). Of interest is the report of Alp et al that not only did circumcision during adulthood not adversely affects ejaculatory function but was associated with significantly longer mean IELTs after circumcision (144). Similarly, Gao et al reported that adult circumcised men experienced significantly improved IELT, control over ejaculation, and satisfaction with sexual intercourse compared to a control group (P<0.001 for all) (145).…”
Section: Circumcision and Pementioning
confidence: 99%
“…Psychotherapy involve education both patients and their partners,which may improve their sexual skills and increase self-confidence and reduce anxiety during sex [7].However, the majority of studies aim to treat PE by psychotherapy didn't meet the criteria for high level evidence based studies [8].The effectiveness of behavior therapy reported was different, with poor compliance of the patient.Although their utility are limited today, they are used to treat PE combined with drugs [9]. Surgical therapy such as ablation and modulation of dorsal penile nerve [10] is an innovative modality need further study and may cause irreversible damage which limit its clinical application.Circumcision seems to have some role in treating PE which can extend the ejaculation time [11],but it could not be interpreted as a justification for circumcision in men with PE even there were no adversely affect ejaculatory function [12].Although drug therapy is widely used for the treatment of PE in clinic, few studies devote to on-demand use of dapoxetine to treat LPE.…”
Section: Resultsmentioning
confidence: 99%